2014
DOI: 10.1155/2014/469693
|View full text |Cite
|
Sign up to set email alerts
|

Separation Process by Porous Membranes: A Numerical Investigation

Abstract: A major problem associated with the membrane separation processes is the permeate flux drop, limiting the widespread of industrial application of this process. This occurs due to the accumulation of solute concentration near the membrane surface. An exact quantification of the concentration polarization as a function of process conditions is essential to estimate the system performance satisfactorily. In this sense, this work aims to predict the behavior of the concentration polarization boundary layer along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…It is observed that the boundary layer grows with the increase in dimensionless length. The discrepancy between the results obtained in this research and those reported by the researchers [12][13][14], is probably due to the fact that their models have used decoupled transport equations, where the velocity profile does not interfere with the concentration profile, and thus the conservation equations of mass and momentum were solved separately. However, in the present research the coupling of the momentum and mass transfer equations was applied, which explains the difference between the two results.…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…It is observed that the boundary layer grows with the increase in dimensionless length. The discrepancy between the results obtained in this research and those reported by the researchers [12][13][14], is probably due to the fact that their models have used decoupled transport equations, where the velocity profile does not interfere with the concentration profile, and thus the conservation equations of mass and momentum were solved separately. However, in the present research the coupling of the momentum and mass transfer equations was applied, which explains the difference between the two results.…”
Section: Resultscontrasting
confidence: 84%
“…Mathematical Model. To study the separation process by microfiltration using the twodimensional tubular membrane modules, based on the literature [12][13][14][15][16], in a general manner, following considerations were assumed that: the viscosity and density of fluids are constant and equals to the pure solvent, as represented in Table 1; The solute diffusion coefficient is considered constant; The flow is incompressible, isothermal and steady state; The local wall permeation velocity is determined from the resistance-in-series model, and the concentration layer is assumed to be homogeneous and the Carmen-Kozeny equation is valid.…”
Section: Methodology and Mathematical Modelingmentioning
confidence: 99%
“…According to Cunha (2014), it is important to have a control of the mesh quality in order to have a control of the discretization errors. In other words, to obtain more accurate numerical solutions it is important to reduce their source of errors.…”
Section: Mesh Generationmentioning
confidence: 99%
“…Besides, solute accumulation at interface membrane/solution is inevitable. Because of the importance, several studies involving the membrane separation process with computer codes' aid based on CFD tools (Computational Fluid Dynamics) have been conducted, for example, Porciúncula [9], Vieira et al [13], Souza [14], Cunha [15], Cunha et al [16], Cunha et al [17], Magalhães et al [18], Souza et al [19], Magalhães et al [20], Oliveira [21] and Magalhães et al [22].…”
Section: Introductionmentioning
confidence: 99%